Cooperative Chiral Guanidine/AgPF6 Catalyzed Asymmetric Isocyanoacetate Aldol Reaction with Isatins - Lu, Yan; Wang, Min; Zhao, Xiaohu; Liu, Xiaohua; Lin, Lili; Feng, Xiaoming (Synlett, 2015)
A cooperative chiral guanidine/Ag(I) catalyst system was developed for the asymmetric isocyanoacetate aldol reaction with isatins. The corresponding chiral spirooxindole oxazolines were obtained in good yields (up to 99%), moderate diastereoselectivities (up to 88:12 dr) and good enantioselectivities (up to 90% ee).
Keywords: aldol reaction; cooperative catalysis; isatins; isocyanoacetates; guanidine